Iron deposition causes oxidative stress, inflammation and fibrosis in carbon tetrachloride-induced liver dysfunction in rats - Reza, Hasan Mahmud; Sagor, Md. Abu Taher; Alam, Md. Ashraful (Bangladesh Journal of Pharmacology, 2015)
The present study investigates the pathological implications of parenchymal iron overload due to CCl4 treatment in liver dysfunction. Sixteen female rats were randomly divided into control and CCl4 treated groups. The serum levels of tramsaminases, malondialdehyde, advanced protein oxidation product, catalase, and reduced glutathione concentrations in the plasma and hepatic homogenate were determined. Moreover, histopathological changes in liver sections were investigated for inflammatory cell infiltration, fibrosis and iron overload. The administration of CCl4 resulted in increased liver marker enzymes activities and oxidative stress parameters mentioned above compared to control. Moreover, CCl4 administration also decreased antioxidant enzymes activities and increased inflammatory cell infiltration and fibrosis along with iron deposition in liver of rats. These findings indicate that CCl4 may induce hepatic fibrosis and inflammation during CCl4 induced liver injury via iron mediated oxidative damages.